PELATIHAN DIGITALISASI PELAKU UMKM DESA BENDOREJO MELALUI PEMBUATAN TOKO DARING DI TOKOPEDIA DAN TIKTOK SHOP - Lianjuan Najaan Karima; Muhamad Nasrulloh (P3M STAI KH. MUHAMMAD ALI SHODIQ, 2025)
Micro, Small, and Medium Enterprises (MSMEs) in Bendorejo Village, Pogalan District, Trenggalek Regency, produce competitive local products such as tempe sagu, tempe chips, and alen-alen, but are still marketed conventionally. This community service program aimed to enhance the digital skills of MSME actors through training in creating online stores on Tokopedia and TikTok Shop. The implementation method included delivering digital marketing material and hands-on practice in creating online stores, attended by 21 participants. The results showed that 71.4% of participants successfully created online stores and uploaded products, while the rest were constrained by device limitations and account verification issues. Practice-based training proved effective in accelerating digital skills acquisition. Continuous mentoring and infrastructure support are needed to ensure MSMEs can optimally utilize digital platforms.